Lifetime socioeconomic circumstances and chronic pain in later adulthood: findings from a British birth cohort study. Issue 3 (7th March 2019) - Jay, Matthew A; Bendayan, Rebecca; Cooper, Rachel; Muthuri, Stella G
Abstract : Objectives: To investigate associations between a range of different indicators of socioeconomic position (SEP: occupational class, education, household overcrowding and tenure, and experience of financial hardship) across life and chronic widespread and regional pain (CWP and CRP) at age 68. Design: Prospective birth cohort; the Medical Research Council National Survey of Health and Development. Setting: England, Scotland and Wales. Participants: Up to 2378 men and women who have been followed-up since birth in 1946 to age 68. Primary outcome measures: On the basis of their self-report of pain at age 68, participants were classified as: CWP (American College of Rheumatology criteria), CRP (pain of at least 3 months' duration but that does not meet the definition of CWP), other pain (<3 months in duration) or no pain. Results: At age 68, the prevalence of CWP was 13.3% and 7.8% in women and men, respectively, and that of CRP was 32.3% and 28.7% in women and men, respectively. There was no clear evidence that indicators of SEP in childhood or later adulthood were associated with pain. Having experienced (vs not) financial hardship and being a tenant (vs owner-occupier) in earlier adulthood were both associated with an increased risk of CWP; for example, moderate hardship adjusted relative risk ratio (RRRadj ) 2.32 (95% CI: 1.19 to 4.52) and most hardship RRRadj 4.44 (95% CI: 2.02 to 9.77). Accumulation of financial hardship across earlier and later adulthood was also associated with an increased risk of CWP. Conclusions: Consideration of socioeconomic factors in earlier adulthood may be important when identifying targets for intervention to prevent CWP in later life.